What breaks the flow of reading? A study on characteristics of attentional disruption during digital reading - Chevet, Guillaume; Baccino, Thierry; Vinter, Annie; Drai-Zerbib, Véronique (Frontiers in Psychology, 2022)
Reading is increasingly taking place on digital media, which are vectors of attentional disruption. This manuscript aims to characterize attentional disruption during reading on a computer screen in an ecological environment. To this end, we collected information relating to reader interruptions (number, type, duration, position, mental effort, and valence) and self-caught mind wandering (occurrence, position) throughout the reading session for high and low media multitaskers in their own specific ecological environment, at home. Comprehension of the narrative text was assessed both with surface and inferential questions. In total, 74 participants (M = 22.16, SD = 2.35) took part in the experiment. They reported attentional disruptions on average every 4 mins during reading. Moreover, there were more attentional disruptions during the first half of the text. Most interruptions were short and little mental effort was required to process them. We made a distinction between media-related and media-unrelated related interruptions. Multiple linear regression analyses showed that media-unrelated interruptions were actually related to better performance for both inferential and surface level questions. Furthermore, media-related interruptions were more frequent for high than low media multitaskers. Pleasure experienced when reading the text was also a significant predictor of comprehension. The results are discussed with regard to Long-Term Working Memory and strategies that the readers could have implemented to recover the thread of their reading.